Closure - Management, Journal of Infrastructure & Facility Asset (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Journal of Infrastructure & Facility Asset ManagementVolume 6, Issue 1, January 2024 (e) ISSN 2656-8896 (P) ISSN 2656-890X